Bahasa Inggris - Bambang Budiwiranto; Jasmadi Jasmadi; Dewi Maryam; Lutfi Zaimuddin (Universitas Pendidikan Ganesha, 2025)
The need for inclusive communication in farmer empowerment is becoming increasingly urgent in the digital era, especially in rural areas such as Sumberejo Sub-district, Tanggamus Regency, and Lampung, where most people depend on the agricultural sector as the primary source of livelihood. This research explores how inclusive communication can increase farmers' participation in digital technology-based socio-economic activities. Using a qualitative research method with a case study approach, data was collected through semi-structured interviews with farmers' group association administrators, village heads, and agricultural extension officers in 13 villages, as well as direct observation and documentation studies. The results show that inclusive communication that considers the level of digital literacy and local cultural sensitivity can improve farmers' access to information, strengthen social networks, and expand economic opportunities. Farmer group associations (Gapoktan) and agricultural extension officers act as key intermediaries in the technology adoption process, but there are still constraints, such as limited digital infrastructure and lack of technical training. Collaboration between the local government, private sector, and extension agencies is important in creating sustainable empowerment synergies. This research provides theoretical contributions to developing community-based inclusive communication models in the agricultural sector, as well as practical implications for local policies that support digital development in rural areas. Further studies are recommended to explore variables such as gender roles and the influence of social trust in the successful implementation of inclusive communication in farming communities.